Development and fit-for-purpose validation of a LC–MS/MS assay for fibrinogen peptide A quantitation in human plasma. (July 2014) - Lin, Mingxiang; Lassman, Michael E; Weiner, Russell; Laterza, Omar F
Background: Fibrinopeptide A (FPA) is a plasma peptide, formed by the action of thrombin on fibrinogen during clog formation. FPA represents a direct indicator of thrombin activity and could potentially be used as a biomarker for anti-thrombotic therapy development.Results/Methodology: A LC-MS/MS assay with a high throughput solid phase extraction procedure was developed and validated to measure FPA in plasma. The lower limit-of-quantitation (LLOQ) of this assay was determined to be 0.16 nM. The inter- and intra-day%CV was <15%. Freeze–thaw stability of FPA was ±30% up to 3 cycles and linear response of FPA was observed for plasma dilution up to 16-fold.Conclusion: The assay was validated and the biological variability of FPA in plasma was established (1–30 nM).